Factors associated with frequent high-cost individuals with cystic fibrosis and their healthcare utilization and cost patterns - Sameer Desai; Wei Zhang; Jason M. Sutherland; Joel Singer; Bradley S. Quon (Scientific Reports, 2023)
Abstract Cystic fibrosis (CF) is a progressive multi-organ disease with significant morbidity placing extensive demands on the healthcare system. Little is known about those individuals with CF who continually incur high costs over multiple years. Understanding their characteristics may help inform opportunities to improve management and care, and potentially reduce costs. The purpose of this study was to identify and understand the clinical and demographic attributes of frequent high-costing CF individuals and characterize their healthcare utilization and costs over time. A longitudinal study of retrospective data was completed in British Columbia, Canada by linking the Canadian CF Registry with provincial healthcare administrative databases for the period between 2009 and 2017. Multivariable Cox regression models were employed to identify baseline factors associated with becoming a frequent high-cost CF user (vs. not a frequent high-cost CF user) in the follow-up period. We found that severe lung impairment (Hazard Ratio [HR]: 3.71, 95% confidence interval [CI], 1.49–9.21), lung transplantation (HR: 4.23, 95% CI, 1.68–10.69), liver cirrhosis with portal hypertension (HR: 10.96, 95% CI: 3.85–31.20) and female sex (HR: 1.97, 95% CI: 1.13–3.44) were associated with becoming a frequent high-cost CF user. Fifty-nine (17% of cohort) frequent high-cost CF users accounted for more than one-third of the overall total healthcare costs, largely due to inpatient hospitalization and outpatient medication costs.